PLACEMAKING KAWASAN PERMUKIMAN DOME NGLEPEN SEBAGAI KAWASAN DESA WISATA - Pratama, Dandi Raviandaru; Marcillia, Syam Rachma (Jurnal Arsitektur dan Perencanaan (JUARA), 2019)
Dome house is a settlement relocation post-earthquake disaster housing in Nglepen, Yogyakarta. The ability of residents to restore the situation makes this settlement now better known as a tourist village. Placemaking is happening to change the settlement that was built with the concept of relocation of housing into a tourist village. Even from the tourism of these settlements benefit. This study aims to find out how placemaking occurs and the factors that affect in dome settlements. The method used is a qualitative method by identifying the points of variables and indicators in the study area in accordance with the conditions of observation in the field, then process the data generated and analyze it based on related theories. The approach taken is to raise the theory of placemaking. The results showed that the occurrence of placemaking in dome settlements became a tourist village is very high so the need for direction of the development of placemaking can be applied so that the image of dome settlements is maintained.